The economics of post-harvest loss and loss-preventing technologies in developing countries - Ricker-Gilbert, J.; Omotilewa, O.J.; Kadjo, D. (Annual Reviews, 2022)
This article reviews the recent literature that has evaluated the effectiveness of postharvest loss (PHL)-reducing technologies for grains among smallholder farmers and small-scale traders in sub-Saharan Africa. We also develop a conceptual framework for identifying and quantifying different types of PHL that include physical quantity losses along with quality losses that are both observable (e.g., discoloration, insect damage, mold growth, and odor) and unobservable (e.g., aflatoxin contamination, chemical residues, and nutrient content losses). The framework considers how PHL affects producers, consumers, and society as a whole. We find that although reducing postharvest quantity losses often receives more attention from researchers, it is the loss of quality, particularly unobservable quality issues, that has a large effect on food safety and nutrition. A review of the literature suggests that cost-effective technologies to reduce PHL exist, but facilitating their adoption requires action from both the public and private sectors.